'De novo' centrioles originate at sites associated with annulate lamellae in sea-urchin eggs. Issue 11 (November 1982) - Kallenbach, Rein J.
Abstract : Hypertonic stress stimulates the formation of new centrioles in sea-urchin eggs. Those centrioles which appear away from the nuclear surface originate exclusiveJy at sites associated with annulate lamellae. Although apparent when nascent centrioles become visible, the annulate lamellar association is gradually lost as nascent forms mature into centrioles.